Acoustic detection and acoustic habitat characterisation of the critically endangered white‐bellied heron (Ardea insignis) in Bhutan. (10th December 2018) - Dema, Tshering; Towsey, Michael; Sherub, Sherub; Sonam, Jigme; Kinley, Kinley; Truskinger, Anthony; Brereton, Margot; Roe, Paul
Abstract: Growing developmental activities, such as hydropower construction, farm roads, and other human activities, are affecting the critically endangered white‐bellied heron (WBH). Out of a known global population of 60, 28 individuals inhabit the river basin area and freshwater lakes and ponds of Bhutan. Several constraints impede continuous monitoring of endangered species, such as the isolated and cryptic nature of the species and the remoteness of its habitat; to date, there are no long‐term reference data or techniques implemented for continuous monitoring of this species. In this study, we designed acoustic detection and habitat characterisation methods using long‐duration recordings from three habitat areas in Bhutan. Acoustic indices were extracted and used to implement a species‐specific call detector and to generate habitat soundscape representations. Using WBH calls annotated in month‐long recordings from a known site, a novel indices‐based detector was implemented and tested. A total of 960 hr of continuous audio recordings from three habitats in Bhutan were analysed. We found that a species call detector implemented using a combination of acoustic indices (that includes measures of spectral and temporal entropy and different angles of spectral ridges) has a correct detection rate of 81%. Additionally, visual inspection of the species' acoustic habitat using long‐duration false‐colour spectrograms enabled qualitative assessment of acoustic habitat structure and other dominant acoustic events. This study proposes a combined approach of species acoustic detection and habitat soundscape analysis for holistic acoustic monitoring of endangered species. As a direct outcome of this work, we documented acoustic reference data on the critically endangered WBH from multiple habitat areas and have analysed its temporal vocalisation patterns across sites.